2015
DOI: 10.3389/fneur.2015.00216
|View full text |Cite
|
Sign up to set email alerts
|

The Central Biobank and Virtual Biobank of BIOMARKAPD: A Resource for Studies on Neurodegenerative Diseases

Abstract: Biobanks are important resources for biomarker discovery and assay development. Biomarkers for Alzheimer’s and Parkinson’s disease (BIOMARKAPD) is a European multicenter study, funded by the EU Joint Programme-Neurodegenerative Disease Research, which aims to improve the clinical use of body fluid markers for the diagnosis and prognosis of Alzheimer’s disease (AD) and Parkinson’s disease (PD). The objective was to standardize the assessment of existing assays and to validate novel fluid biomarkers for AD and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…In contrast, clinics and diagnostic laboratories have commonly developed their own site-specific protocols for the pre-analytical handling of CSF [14,80]. While some centres have published their protocols, the majority follow a small number of published protocols or recommendations, while a variety of adjustments to these protocols also have been published [35,71,80,[84][85][86][87]. In addition, many unpublished adjustments to pre-analytical protocols have been adopted (Fagan A, personal observation).…”
Section: Rationale For This Systematic Reviewmentioning
confidence: 99%
“…In contrast, clinics and diagnostic laboratories have commonly developed their own site-specific protocols for the pre-analytical handling of CSF [14,80]. While some centres have published their protocols, the majority follow a small number of published protocols or recommendations, while a variety of adjustments to these protocols also have been published [35,71,80,[84][85][86][87]. In addition, many unpublished adjustments to pre-analytical protocols have been adopted (Fagan A, personal observation).…”
Section: Rationale For This Systematic Reviewmentioning
confidence: 99%
“…However, broader reproducibility of the results has not yet been achieved, which is currently seen as, to a high degree, the result of substantial variability across various diagnostic centers in pre-analytical, analytical and post-analytical factors, referring to both the diagnosis of patients recruited for studies, and to the methodology of blood handling and miRNA analysis [47, 48]. Moreover, so far in patients with MCI due to AD only one study reported miRNA signatures that could be directly related not only to neuropsychological tests, but also the levels of CSF biomarkers [87].…”
Section: Introductionmentioning
confidence: 99%
“…All involved patients were diagnosed in adherence to the current golden standards [6, 7]. To respond to the necessity for the extensive standardization of materials and procedures, we employed standardized CSF assays and guidelines for the standardization of pre-analytic variables for blood-based biomarkers established under the international JPND BIOMARKAPD consortium [47]. To further standardize our research, we applied a commercially available qRT-PCR assay comprising 179 miRNAs preselected for blood plasma.…”
Section: Introductionmentioning
confidence: 99%
“…We sought to examine factors influencing agreement to undergo LP as well as factors contributing to LP complications. Building on a survey conducted at European and Canadian memory clinics through the BIOMARKAPD project, 3,4 we prospectively surveyed and documented LP practices, perceptions, agreement rates, and complications at the National Institute on Aging (NIA)-funded Alzheimer’s Disease Centers (ADCs) in the United States over a two-year period.…”
mentioning
confidence: 99%